Blood–brain barrier and brain structural changes in lung cancer patients with non-brain metastases - Zhang, Da-Fu; Ma, Huan; Yang, Guang-Jun; Zhang, Zhi-Ping; He, Yin-Fu; Feng, Mao-Yang; Shan, Bao-Ci; Xu, Xiu-Feng; Ding, Ying-Ying; Cheng, Yu-Qi (Frontiers in Oncology, 2022)
Purpose: To explore the relationship between blood-brain barrier (BBB) leakage and brain structure in non-brain metastasis lung cancer (LC) by magnetic resonance imaging (MRI) as well as to indicate the possibility of brain metastasis (BM) occurrence. Patients and methods: MRI were performed in 75 LC patients and 29 counterpart healthy peoples (HCs). We used the Patlak pharmacokinetic model to calculate the average leakage in each brain region according to the automated anatomical labeling (AAL) atlas. The thickness of the cortex and the volumes of subcortical structures were calculated using the FreeSurfer base on Destrieux atlas. We compared the thickness of the cerebral cortex, the volumes of subcortical structures, and the leakage rates of BBB, and evaluated the relationships between these parameters. Results: Compared with HCs, the leakage rates of seven brain regions were higher in patients with advanced LC (aLC). In contrast to patients with early LC (eLC), the cortical thickness of two regions was decreased in aLCs. The volumes of twelve regions were also reduced in aLCs. Brain regions with increased BBB penetration showed negative correlations with thinner cortices and reduced subcortical structure volumes (P<0.05, R=-0.2 to -0.50). BBB penetration was positively correlated with tumour size and with levels of the tumour marker CYFRA21-1 (P<0.05, R=0.2–0.70). Conclusion: We found an increase in BBB permeability in non-BM aLCs that corresponded to a thinner cortical thickness and smaller subcortical structure volumes. With progression in LC staging, BBB shows higher permeability and may be more likely to develop into BM.